2016
DOI: 10.1111/evj.12568
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a wireless activity monitoring system to quantify locomotor activity in horses in experimental settings

Abstract: The dual-mode accelerometric device was sufficiently accurate to quantify and compare locomotor activity in horses moving at different speeds and gaits. Positioning the device on the hindlimb allowed for the most accurate results. The step count function can be useful but must be manually corrected, especially at the walk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…Use of this specific accelerometer a for behavioral data collection has been validated in dairy cows 50 but not in horses; however, the general use of triaxial accelerometers has been validated in horses. 51,52 Furthermore, placement of the accelerometer on a hind limb, as was done in the present study, reportedly yields the most accurate data. 51 In a study 53 involving calves, use of an accelerometer to examine the effect of castration revealed that castrated calves spent a significantly larger amount of time standing during the subsequent 24-hour period (or longer) than uncastrated calves, but studies [54][55][56] of the effect of lameness on cattle behavior have shown that lame cattle spend more time lying down than do nonlame cattle.…”
Section: Discussionsupporting
confidence: 51%
“…Use of this specific accelerometer a for behavioral data collection has been validated in dairy cows 50 but not in horses; however, the general use of triaxial accelerometers has been validated in horses. 51,52 Furthermore, placement of the accelerometer on a hind limb, as was done in the present study, reportedly yields the most accurate data. 51 In a study 53 involving calves, use of an accelerometer to examine the effect of castration revealed that castrated calves spent a significantly larger amount of time standing during the subsequent 24-hour period (or longer) than uncastrated calves, but studies [54][55][56] of the effect of lameness on cattle behavior have shown that lame cattle spend more time lying down than do nonlame cattle.…”
Section: Discussionsupporting
confidence: 51%
“…In this study Martin Fries and colleagues in Switzerland evaluated a wireless activity monitoring system to quantify locomotor activity in horses in experimental settings .…”
Section: Quantifying Locomotor Activitymentioning
confidence: 99%
“…Pedometers (or accelerometer devices with bespoke equine algorithms) may be useful for quantitative measurement of limb weight shifting frequency in horses at risk of developing supporting limb laminitis and could also provide an indication of locomotor activity (Fries et al . ) in horses with laminitis as a measure of the efficacy of an analgesia protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Pain management for laminitis of locomotor activity (Fries et al 2017) in horses with laminitis as a measure of the efficacy of an analgesia protocol.…”
mentioning
confidence: 99%